IDENTIFIKASI KADAR LOGAM TEMBAGA (Cu) DAN BESI (Fe) DALAM AIR LAUT DI WILAYAH PESISIR JEMBATAN PURI KOTA SORONG - Ainul Alim Rahman; Firmanullah Fadlil (AGITASI: Jurnal Teknik Kimia, 2026)
The determination of the heavy metals Copper (Cu) and Iron (Fe) in seawater in the coastal area of ​​Jembatan Puri, Sorong City, was conducted using the Ultra Violet Visible (UV-Vis) Spectrophotometry method. This study was conducted to determine heavy metal pollution in the coastal waters of Jembatan Puri, Sorong City. Samples were taken from two different locations. Sample preparation was carried out by wet digestion and analyzed using the Ultra Violet Visible (UV-Vis) Spectrophotometry method. The results of the seawater analysis showed that the levels of Cu and Fe metals at each location were (8.6325 ppm; 8.5901 ppm, 8.5901 ppm), (0.6411 ppm; 0.6077 ppm, 0.6578 ppm). The concentrations of Cu and Fe metals were above the quality standard threshold set by the Minister of Environment in 2004.